Uji Toksisitas Jamur Metarhizium anisopliae terhadap Hama Ulat Krop Kubis Crocidolomia binotalis Zell. - Siska Agustina Pertiwi; Nanang Tri Haryadi (Universitas Merdeka Madiun, 2022)
Cabbage head caterpillar Crocidolomia binotalis Zell. caused up to 79.81% damage to cabbage plants. Metarhizium anisopliae is an entomopathogenic fungus that is often used for pest control in the field because it is toxic to various phases of insect life. This study aimed to determine the toxicity ability of the fungus Metarhizium anisopliae in controlling the population of the cabbage head caterpillar Crocidolomia binotalis Zell. in the laboratory. The research was conducted at the Laboratory of Agrotechnology, Faculty of Agriculture, University of Jember. The study used a Completely Randomized Design with 5 treatments and 4 replications in order to obtain 20 experimental units. The treatments used in this study were as follows: A = Control (aquadest); B = density 104 conidia/ml; C = density 105 conidia/ml; D = 106 conidia/ml; and E = 107 conidia/ml. The results showed that in the laboratory test the density of the fungus Metarhizium anisopliae 107 conidia/ml caused the highest mortality of 92.50%, while the lowest mortality percentage was 22.50% in the treatment of 104 conidia/ml on 7 days of observation. The results of the LT50 calculation showed that the most effective density was 106 conidia/ml with an LT50 value on the 4th day. The most effective density of Metarhizium anisopliae, 106 conidia/ml, was recommended for use in population control of the cabbage head caterpillar Crocidolomia binotalis Zell. because it is capable of causing the death of 50% of the population of Crocidolomia binotalis Zell. with the fastest time of about 4 days.